Strategic management of technological innovation. - Schilling, Melissa A., ....- (Boston : McGraw-Hill, 2008)
"Strategic Management of Technological Innovation, 2e" by Melissa Schilling is the first comprehensive, rigorous and yet accessible text for the Technology and Innovation Management course. Unlike other books, Schilling's approach synthesizes the major research in the field, providing students with the knowledge needed to enhance case discussion and analysis. The subject is approached as a strategic process, and as such, is organized to mirror the strategic management process used in most strategy textbooks, progressing from assessing the competitive dynamics of a situation, to strategy formulation, to strategy implementation. As a brief, affordable paperback, it is ideal to package with cases. Recommended case sets from the author are available through the Primis Custom Case Database or from the Harvard Business School Case Database.
Keywords: Bedrijfsstrategie; Productontwikkeling; Strategisch management; Technologische innovatie